It takes two to tango: The use of social network theory in explaining knowledge production through research networks - Frick, Liezel B; Hoffman, LC (South African Journal of Higher Education, 2016)
Contemporary society presents researchers with complex problems that often demand collaborative inquiry to extend the existing knowledge boundaries. Research networks give researchers access to to a wider pool of expertise in solving such complex problems. This article uses social network theory to explore the different ways in which such networks are formed. Network formation is based on ties that are belonging, bonding or binding, which may influence how resources become accessible and distributed. We argue that research networks can be formed in all three these ways, and that universities exist amidst such multiple networks. An ecological understanding of the multiplicity of network formation may enable universities and academics to foster a variety of approaches to establishing and supporting knowledge production through research networks – implying a functional relationship akin to the delicate balance between tango dancers and the music.